Neurolinguistic Programming applied to teaching-learning processes - MARTÍNEZ-MARTÍNEZ, Malinali Xochiquetzal; Mauricio, FLORES-AGUILAR (Journal of Systems and Educational Management, 2022)
The purpose of this article is to analyze the elements used in the teaching of classes at the Universidad Tecnológica del Norte de Aguascalientes (UTNA), seeking to develop a reflection in relation to the pieces that students consider necessary for effective learning and understanding of the topics of study. Living conditions, the customs, the particular characteristics of a sector of the population or geographic area, and the use of new technologies have as a consequence that the study models and the techniques or tools that young people use for the development of their education suffer continuous changes. Consequently, to believe or expect that the elements of the development of a class should be standardized, remain inert, and also, ensure the understanding and continuous interest of young people is too ambitious; This is why the main point is to obtain the vision that young people have of the elements they consider necessary for effective learning in the classroom.